2015
DOI: 10.1111/cas.12697
|View full text |Cite
|
Sign up to set email alerts
|

Cooperatively transcriptional and epigenetic regulation of sonic hedgehog overexpression drives malignant potential of breast cancer

Abstract: Sonic hedgehog (Shh), a ligand of Hedgehog signaling pathway, is considered an important oncogene and an exciting potential therapeutic target in several cancers. Comprehensive understanding of the regulation mechanism of Shh in cancer cells is necessary to find an effective approach to selectively block its tumorigenic function. We and others previously demonstrated that nuclear factor-kappa B (NF-κB) activation and promoter hypomethylation contributed to the overexpression of Shh. However, the relationship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…Moreover, overexpression of Shh was found in breast cancer tissues and survival analysis suggested that Shh overexpression was a poor prognosis indicator for breast cancers [8]. These evidence characterized that Shh overexpression was a critical event in breast carcinogenesis [8,9]. In addition, Shh activation induced transcription of hexokinase 2 (HK2) and pyruvate kinase M2 (PKM2) and caused a robust increase of glycolytic metabolism in medulloblastoma [10].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, overexpression of Shh was found in breast cancer tissues and survival analysis suggested that Shh overexpression was a poor prognosis indicator for breast cancers [8]. These evidence characterized that Shh overexpression was a critical event in breast carcinogenesis [8,9]. In addition, Shh activation induced transcription of hexokinase 2 (HK2) and pyruvate kinase M2 (PKM2) and caused a robust increase of glycolytic metabolism in medulloblastoma [10].…”
Section: Introductionmentioning
confidence: 98%
“…In human hepatocellular carcinoma (HCC), Shh signaling pathway mediates cancer cells invasion and metastasis by increasing MMP-9 expression via ERK pathway [7]. Moreover, overexpression of Shh was found in breast cancer tissues and survival analysis suggested that Shh overexpression was a poor prognosis indicator for breast cancers [8]. These evidence characterized that Shh overexpression was a critical event in breast carcinogenesis [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…These data suggest that impaired activation of ERK1/ 2 signaling may serve as a mechanism underlying the inhibited up-regulation of SHH expression by marrow hematopoietic cells during systemic E. coli infection in mice acutely intoxicated with alcohol. In addition to SP1, studies have shown that other transcription factors including NF-jB and STAT6 may participate in the regulation of SHH expression (Duan et al, 2015;Wang et al, 2020). During infection and inflammation, cytokines and other endogenous mediators can signal through these transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…So the target genes of Glis were activated, including SOX2 [13] and PTCH1 [14]. It has been well demonstrated that the activation of Shh signaling was involved in the development and progression of many types of cancer [15][16][17][18], including ESCC [19,20]. Moreover, the critical roles of Shh pathway in maintaining cancer stem cells (CSCs) and drug resistance have also been well illustrated [13,21,22].…”
Section: Introductionmentioning
confidence: 99%